Addressing Korea's Long-Term Fiscal Challenges - Syed, Murtaza (IMF Working Papers; Working Paper ;, 2008)
Korea is on the verge of an unprecedented demographic shift. In coming decades, rapid aging will transform it from one of the youngest populations in the OECD to among the oldest in record time. In turn, this shift will put tremendous pressure on the pension system and health and long-term care expenditures. This paper evaluates the impact of population aging on the long-term fiscal position in Korea, and assesses potential policy responses using the IMF's Global Fiscal Model. The paper finds that the key to maintaining a sound long-run fiscal position is to act early and with a range of policy tools, including pension reform, tax base broadening (and, if necessary, rate hikes), improved tax administration and some expenditure reallocation.